The Relationship of 67Ga Uptake to Citrate Dose, Compared with 67Ga-Chloride and 67Ga-Transferrin in Rodent Tissues and Tumours - Hammersley, P. A. G.; Zivanovic, Maureen A. (Nuklearmedizin - NuclearMedicine, 1980)
The uptake of 67Ga-citrate in the tissues of the mouse and rat and in two mouse tumours, S180 and PC6, has been measured and shown to be independent of the citrate concentration of the injection dose. The tumour uptake and tissue distribution of 67Ga-chloride and 67Ga-transferrin were identical with those of the citrate complex. Whole-body retention data for h7Ga-citrate in the mouse for 14 days after injection are also presented.